Luminescence Vapochromism of a Dynamic Copper Iodide Mesocate. Issue 71 (16th November 2018) - Benito, Quentin; Balogh, Cristina M.; El Moll, Hani; Gacoin, Thierry; Cordier, Marie; Rakhmatullin, Aydar; Latouche, Camille; Martineau‐Corcos, Charlotte; Perruchas, Sandrine
Abstract: A copper iodide complex coordinated by three phosphine ligands with the formula [Cu2 I2 (Ph2 PC2 (C6 H4 )C2 PPh2 )3 ] exhibits solvatochromic and vapochromic luminescence properties. A mechanism based on solvent‐dependent molecular motion appears to occur. The highly contrasted response observed upon THF solvent exposure makes this complex an appealing candidate for chemical sensor applications. Abstract : On or off? This study reports the luminescence vapochromic properties of a copper iodide complex with specific response to THF. With a turn‐on response opposite to common quenching effect, the highly contrasted signal enables direct observation by the naked eye.